Chinese cyber nationalism : evolution, characteristics, and implications - Wu, Xu, 1969- (Lexington Books, 2007)
Chinese Cyber Nationalism offers the first comprehensive examination of the social and ideological movement that mixes Confucian cultural traditions and advanced media technology. Over the past decade, the Internet has increasingly become a communication center, organizational platform, and channel of execution by which Chinese nationalistic causes have been promoted throughout the world.